O testemunho em Auto-retrato, de João Melo - Rendelli, Debora Ribeiro (2022)
The present dissertation focuses on the work of João Melo, Self-portrait, to analyze the testimonial content that makes it an important work for the history of Angola, in a sense that over this much was written, rewritten and erased. The entire foundation of this work is supported by authors who discuss the topic of post-coloniality, such as Stuart Hall, Ana Mafalda Leite, Inocência Mata, Homi Bhabha, Boaventura Sousa Santos, among others. The difficulty in placing colonized countries on an equal footing with their first world colonizers invades the theoretical and practical spheres, but a light is shed by the authors' dialogue on the situation of Angola in the 21st century, by João Melo, which has of literary artifices of excellence to produce a work with a deep testimonial content to ensure that the memory of his ancestors lives, in addition to having a visible dexterity in the description of everyday life and its nuances, in Melo's work can be seen an exaltation of life, in order to make an important counterpoint to the ills present in Angola, and extremely useful for the aid of a national identity, which is sought by the author and his literary generation. On top of the author's action, we find a possible way of meaning of the poems written in Self-portrait based on operators of meaning defined so that we can participate in the mission set as witnesses, and carry forward Melo's vision the historical and cultural aspects to which the the Angolan people was subjected and that their memories become so important so that there is a national evolution coming from the reflections that literature is able to provide and when united to history, in an adorned and fluid way, in the language of poiesis, it becomes a tool that in addition to being beautiful, also effective, as João Melo's poetic language bequeaths us